2020
DOI: 10.1177/1362361320942981
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the convergence of self-report and informant measures for adults with autism spectrum disorder

Abstract: Self-report measures are widely used for research and clinical assessment of adults with autism spectrum disorder. However, there has been little research examining the convergence of self- and informant-report in this population. This study examined agreement between 40 pairs of adults with autism spectrum disorder and their caregivers on measures of symptom severity, daily living skills, quality of life, and unmet service needs. In addition, this study examined the predictive value of each reporter for objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 52 publications
0
18
2
Order By: Relevance
“…Also, proxies reported that more additional services were needed than adults reported themselves. By contrast, no differences between the two forms of report were found regarding current ASC symptoms (Sandercock et al, 2020), although this finding is inconsistent with previous research (Lever & Geurts, 2018). However, it is unknown whether there are informant discrepancies when it comes to the social support network of adults with an ASC, even though information about possible discrepancies could be of value for effective support.…”
contrasting
confidence: 81%
“…Also, proxies reported that more additional services were needed than adults reported themselves. By contrast, no differences between the two forms of report were found regarding current ASC symptoms (Sandercock et al, 2020), although this finding is inconsistent with previous research (Lever & Geurts, 2018). However, it is unknown whether there are informant discrepancies when it comes to the social support network of adults with an ASC, even though information about possible discrepancies could be of value for effective support.…”
contrasting
confidence: 81%
“…Additionally, in order to capture the broad scope of MtD across the lifespan, both pediatric and adult populations were included, which required that our respondents were a mix of patients themselves and caregivers responding on the patient's behalf. This methodology has been used in other diseases where presentation occurs across the age-spectrum, such as sickle cell disease, cerebral palsy, autism and encephalitis [31] , [32] , [33] , [34] , [35] . While the identity of the respondent was controlled for in our model and not found to be a significant predictor of RMBs, it is possible that in a larger or different sample, patients themselves may answer differently than their caregivers [36] .…”
Section: Discussionmentioning
confidence: 99%
“…All diagnoses were self‐reported by the participants. Individuals who self‐diagnose were included, as self‐reporting has precedents in other research, and self‐report and informant measures have been shown to be highly accurate 35–37 . Further, many people (e.g., females and adults) still struggle to receive an assessment and diagnosis of autism in the United Kingdom due to long wait times and other complicating factors 38,39 …”
Section: Methodsmentioning
confidence: 99%
“…Individuals who self-diagnose were included, as self-reporting has precedents in other research, and self-report and informant measures have been shown to be highly accurate. [35][36][37] Further, many people (e.g., females and adults) still struggle to receive an assessment and diagnosis of autism in the United Kingdom due to long wait times and other complicating factors. 38,39 Significantly more autistic participants reported an additional need than non-autistic participants; χ 2 (1, 80) = 21.517, p < .001, d = 1.200.…”
Section: Methodsmentioning
confidence: 99%